The effects of two different explosive strength training programs on vertical jump performance in basketball - Ciacci, S.; Bartolomei, S. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of this study was to compare the effects of two different training programs oriented to improve vertical jump performance and leg stiffness in basketball players. METHODS: Fifty-eight male basketball players were involved, divided into three age groups (senior, U19 and U17). Subsequently, within any age group, the players were randomLy divided into two training groups, respectively performing a 16-week "hang-clean" training program (HCL), and a "half-squat" training program (HSQ), lasting for the same duration. HCL was based on the hang clean exercise and included also jump rope training; HSQ was based on the half squat exercise and included also speed ladder training. The squat jump (SJ), the countermovement jump without and with arm swing, and with one step approach (respectively, CMJ, CMJS, and TCMJS) and explosive strength indices obtained with a leg stiffness test were assessed pre- and post-training. RESULTS: In senior and U19 athletes both training programs involved an improvement of Vertical Jump performance, with some differences between different age groups. Instead, for the U17 players, only the HSQ led to an enhancement of SJ and TCMJS. Significant enhancement of leg stiffness was observed only in U19 and U17 groups after training. CONCLUSIONS: The present study showed that the programs based on the hang-clean and half squat allowed to improve explosive strength in basketball training. However, only HSQ was effective for the U17 group. Thus, the present findings demonstrate that specific training programs should be designed according to the age of the players.